(untitled) - Machlis, Joseph (New York, 1979)
This book is divided into three main sections: the development of twentieth-century concepts, minor and major developments in Europe, and The American scene.
Keywords: Âm nhạc,Music; Lịch sử và phê bình,History and criticism; Thế kỷ 20,20th century